Anita de monte laughs last ebook - Gonzalez, Xochitl (2024)
REESE'S BOOK CLUB PICK New York Times bestselling author Xochitl Gonzalez delivers a mesmerizing novel about a first-generation Ivy League student who uncovers the genius work of a female artist decades after her suspicious death A Best Book of 2024: Kirkus, TIME, NPR, Goodreads, Electric Lit and more! " Anita de Monte Laughs Last is a cry for justice. Writing with urgency and rage, Gonzalez speaks up for those who have been othered and deemed unworthy, robbed of their legacy." ―The Washington Post " Anita De Monte Laughs Last by Xochitl Gonzalez asks some big questions, like who in art or history is remembered, who is left behind or erased and WHY. I have goosebumps just talking about this story." ― Reese Witherspoon 1985. Anita de Monte, a rising star in the art world, is found dead in New York City; her tragic death is the talk of the town. Until it isn't. By 1998 Anita's name has been all but forgotten—certainly by the time Raquel, a third-year art history student is preparing her final thesis. On College Hill, surrounded by privileged students whose futures are already paved out for them, Raquel feels like an outsider. Students of color, like her, are the minority there, and the pressure to work twice as hard for the same opportunities is no secret. But when Raquel becomes romantically involved with a well-connected older art student, she finds herself unexpectedly rising up the social ranks. As she attempts to straddle both worlds, she stumbles upon Anita's story, raising questions about the dynamics of her own relationship, which eerily mirrors that of the forgotten artist. Moving back and forth through time and told from the perspectives of both women, Anita de Monte Laughs Last is a propulsive, witty examination of power, love, and art, daring to ask who gets to be remembered and who is left behind in the rarefied world of the elite.